Impacto do atletismo paralímpico na qualidade de vida de pessoas com deficiência física - Medeiros, Robson da Silva (2014)
Quality of life (QOL) and well-being have been a concern of the population in general, and for many, sport is a means to achieve it. People with physical disabilities in the sport initially sought in sport, a chance of recovery, social integration and well-being. Recently, paralympic sport has become increasingly professional with the presence of paralympians high yield, which has ensured greater opportunities and possibly better QOL for these individuals. The objective of this study was to evaluate quality of life (QOL) of individuals with physical disabilities, practitioners of paralympic athletics, according to the level of competitive sport (elite vs. participation) and compare them with sedentary people with physical disabilities or healthy sedentary. The study included 228 individuals, divided into four groups, matched for age and sex. G1 group - people with physical disabilities practitioners of athletics, elite level; G2 - people with physical disabilities practitioners of athletics, participation level; G3 - sedentary people with physical disabilities and G4 - sedentary healthy people. QOL was measured by the WHOQOL-BREF questionnaire. A comparison of the scores of WHOQOL-BREF was performed by ANOVA with Bonferroni post-test. Each group consisted of 57 volunteers, 41 male and 16 female. The mean age was 31 years (SD = ± 9.6 years). We observed greater overall satisfaction with QOL in G1 compared to G2 (p = 0.00), with no significant difference in domains of the WHOQOL-BREF. Compared with G4, G1 had the best result in the psychological domain and the total score; G2 was better than G4 in the psychological domain, with no difference for the other domains. G1, G2 and G4 groups had higher QOL scores than G3. The results showed that practitioners of athletics with physical disabilities had better QoL compared to sedentary people with physical disabilities or healthy sedentary. The paralympic elite athletes reported better overall satisfaction with QOL than other athletes, however, with no significant difference in QOL domains assessed by the WHOQOL-BREF.